Kontinuität und Diskontinuität in der Reinheitsthematik vom Judentum des zweiten Tempels zum Neuen Testament - Paganini, Simone (Zeitschrift für katholische Theologie, 2012)
Purity and the transmission of impurity were of increasing importance in Judaism during the Second Temple period. They served as identity-forming symbols for large parts of various Jewish communities. The scrolls from Qumran bear witness to the ever more elaborate regulations surrounding the treatment of purity and impurity. With the historical Jesus, however, we find not only a comparative lack of interest in these issues, but also a surprising approach to Jewish concerns. For Jesus, it is not impurity that is infectious, but holiness. While in continuity with Judaism by incorporating the discussion of purity issues, Jesus own treatment of it is also in discontinuity with Second Temple Judaism.